Sulforaphane Prevents Cognitive Decline and Mitochondrial Failure Induced by Hippocampal Expression of Caspase-3 Cleaved Tau - Ampuero-Llanos, E (Elsevier Ltd, 2025)
Caspase-3 cleaved tau (truncated tau) is a pathological modification in tau protein that contributes to neurofibrillary tangle formation (NFTs) and neurodegeneration in AD. Our previous studies indicate that truncated tau affects mitochondrial health, synaptic plasticity, and cognitive performance. Therefore, we studied the effects of sulforaphane (SFN), a natural compound activator of the NRF2 antioxidant pathway present in vegetables and sprouts, on neurodegeneration and cognitive decline induced by truncated tau expression in vivo. We induced a 2-month hippocampal expression of GFP, full-length (AAV-Syn-GFP-T4) and truncated tau (AAV-Syn-GFP-T4C3) using a stereotaxic injection of adeno-associated-virus-9 (AAV9) linked to GFP and a synapsin neuronal promoter in tau (−/−) mice. Hippocampal tau-expressing mice were treated with SFN, and their cognitive performance (NOR, NOL, and Barnes maze tests) and hippocampal mitochondrial function were analyzed. Interestingly, hippocampal truncated tau expression significantly affected cognitive and memory abilities, accompanied by increased ROS and severe mitochondrial dysfunction (depolarization, ATP loss, dynamics de-regulation). Notably, the treatment with SFN (50 mg/kg/day, i.p., two weeks) prevented cognitive impairment and reduced mitochondrial bioenergetics and dynamics defects induced by hippocampal truncated tau expression. These findings suggest a potential role of SFN in ameliorating cognitive loss and mitochondrial impairment promoted by tau pathology in neurological disorders (NDs). © 2025 Elsevier Ltd